'The prison of the body': school uniforms between discipline and governmentality. Issue 1 (2nd January 2023) - Friedrich, Jasper; Shanks, Rachel
ABSTRACT: This article asks what uniform practices in schools can tell us about how power functions through a comprehensive analysis of the uniform policies of all Scottish state secondary schools ( n = 357). Against the backdrop of large-scale shifts from disciplinary societies to ones dominated by 'neoliberal governmentality' identified by Foucault and others, we investigate how these modes of power seem to be entangled in school uniform policies. The analysis reveals the specification of detailed uniform policies that both homogenise, divide and hierarchise the school body, suggesting that disciplinary techniques are alive and well. However, in the justifications that schools provide, we see uniform policies framed not as a tool to enforce discipline, but rather as a technique for pupils to fashion themselves into respectable and employable future adults. We suggest the rise of a 'neoliberal governmentality' has shaped how schools justify their practices of control more than it has shaped the practices themselves.